An energy track method for early-stage rub-impact fault investigation of rotor system. (6th January 2022) - Zhang, Xiantao; Yang, Yongfeng; Shi, Mingming; Zhang, Yamei; Wang, Ping
Highlights: Vibration energy method can help to distinguish sight early-stage rub-impact fault. Novel energy track model can manifest the aggravating process of early-stage fault. Efficiency and accuracy of the energy track model are validated by experiments. Abstract: Rubbing between rotor and stator may cause structural damage and lead to serious accidents. Diagnosing early-stage faults and determining the severity of rub-impact is of great significance for reducing the probability of rub-impact fault. At present, the conventional approaches based on the structure vibration displacement, velocity, acceleration, stress, and mode shape information are used to analyze and even diagnose faults. However, due to the slight impact force and the unobvious dynamic response characteristics, it is difficult to diagnose the early-stage faults accurately by applying those approaches. In this paper, a novel vibrational energy track method is adopted to diagnose the early-stage rub-impact faults. Aiming at a rotor rub-impact model considering the bending and torsional coupled vibration, a numerical method is applied to investigate the dynamic responses when early-stage rub-impact faults occur. Meanwhile, the dynamic response characteristics of early-stage faults and no rub condition are compared. Then, the strain energy theory and the energy track method are introduced to judge the faults. Finally, the energy track method is verified by experiments. The numerical and experimental results show that introducing the energy theory, especially using the energy track method can diagnose the early-stage rub-impact faults, by which the severity of faults can be well manifested. The method proposed in this paper provides a general and effective approach for the diagnosis of early-stage rub-impact faults of rotor.